Prostate cancer, miRNAs, metallothioneins and resistance to cytostatic drugs - Pekarik, V; Gumulec, J; Masarik, M; Kizek, R; Adam, V (Current medicinal chemistry, 2013)
MicroRNAs (miRNAs) translationally repressing their target messenger RNAs due to their gene-regulatory functions play an important but not unexpected role in a tumour development. More surprising are the findings that levels of various miRNAs are well correlated with presence of specific tumours and formation of metastases. Moreover, these small regulatory molecules play a role in the resistance of cancer cells to commonly used anti-cancer drugs, such as cisplatin, anthracyclines, and taxanes. In that respect, miRNAs become very attractive target for potential therapeutic interventions. Improvements in the sensitivity of miRNAs detection techniques led to discovery of circulating miRNAs which became very attractive non-invasive biomarker of cancer with a substantial predictive value. In this review, the authors focus on i) oncogenic and anti-tumour acting miRNAs, ii) function of miRNAs in tumour progression, iii) possible role of miRNAs in resistance to anticancer drugs, and iv) diagnostic potential of miRNAs for identification of cancer from circulating miRNAs with special emphasis on prostate cancer. Moreover, relationship between miRNAs and expression of metallothionein is discussed as a possible explanation of resistance against platinum based drugs.
Keywords: Prostatic Neoplasms; cytostatické látky; nádory prostaty; Cytostatic Agents; mikro RNA; Humans; metalothionein; mužské pohlaví; Male; lidé; chemorezistence; Drug Resistance, Neoplasm; Metallothionein; MicroRNAs